Exploring the contributions of major emission sources to PM2.5 and attributable health burdens in China. (1st April 2023) - Li, Yong; Xue, Liyang; Tao, Yan; Li, Yidu; Wu, Yancong; Liao, Qin; Wan, Junyi; Bai, Yun
Abstract: Ambient fine particulate matter (PM2.5 ) pollution is the principal environmental risk factor for health burdens in China. Identifying the sectoral contributions of pollutant emissions sources on multiple spatiotemporal scales can help in the formulation of specific strategies. In this study, we used sensitivity analysis to explore the specific contributions of seven major emission sources to ambient PM2.5 and attributable premature mortality across mainland China. In 2016, about 60% of China's population lived in areas with PM2.5 concentrations above the Chinese Ambient Air Quality Standard of 35 μg/m 3 . This percentage was expected to decrease to 35% and 39% if industrial and residential emissions were fully eliminated. In densely populated and highly polluted regions, residential sources contributed about 50% of the PM2.5 exposure in winter, while industrial sources contributed the most (29–51%) in the remaining seasons. The three major sectoral contributors to PM2.5 -related deaths were industry (247, 000 cases, 35%), residential sources (219, 000 cases, 31%), and natural sources (87, 000, 12%). The relative contributions of the different sectors varied in the different provinces, with industrial sources making the largest contribution in Shanghai (65%), while residential sources predominated in Heilongjiang (63%), and natural sources dominated in Xinjiang (82%). The contributions of the agricultural (11%), transportation (6%), and power (3%) sources were relatively low in China, but emissions mitigation was still effective in densely populated areas. In conclusion, to effectively alleviate health burdens across China, priority should be given to controlling residential emissions in winter and industrial emissions all year round, taking additional measures to curb emissions from other sources in urban hotspots, and formulating air pollution control strategies tailored to local conditions. Graphical abstract: Image 1 Highlights: Residential sources in highly polluted areas contributed >50% of winter PM2.5 . The industrial sector contributed to >45% of premature deaths in coastal provinces. Eliminating industrial and residential emissions would save 247, 000 and 219, 000 lives annually. Certain pollution levels were almost impossible to eliminate due to natural emissions.